AI and the future of leadership : opportunities and threats for hybrid organizations - Jarvis, Adrian (Routledge focus on business and management., 2026)
AI and the Future of Leadership explores the profound implications of artificial intelligence for leadership theory and practice. As Artificial Intelligence technologies become increasingly embedded in organisational life, this book interrogates the readiness of current leadership models to adapt to an era of automation, algorithms, and accelerated change. Blending critical insight with real-world relevance, the book examines the promises and perils of AI in the workplace-from wellbeing and resistance to innovation and control. It highlights the limits of conventional leadership paradigms and proposes a new framework for 'hybrid intelligence leadership'suited to the complexities of human-machine collaboration. Designed to stimulate debate and advance understanding, this book offers fresh perspectives for scholars and practitioners navigating the fast-evolving AI landscape. It equips readers to think strategically and ethically about leadership in organisations that are increasingly shaped by intelligent systems. It will appeal to academics, researchers, educators and advanced students in leadership, management, and organisational studies. It will also be of interest to professionals and policymakers seeking to understand how leadership must evolve to meet the demands of the AI age.